Quantum-consistent superstring models in four dimensional space-time - Nurmagambetov, A.J. (Вопросы атомной науки и техники, 2009)
Extra space-time dimensions are predicted by String theory. However, up to date there are not any experimental signals in favor of their existence. It forces to search for consistent string theory formulations in four space-time dimensions. The task can be completed with extending the standard vector-type coordinates of four-dimensional space-time with additional tensorial-type bosonic coordinates. The reason of introducing the new set of coordinates is discussed, and calculations of the critical dimension in the Neveu-Schwarz-Ramond tensorial superstring formulation are performed. It is also discussed the role of the new coordinates in the construction of the consistent five-dimensional superstring formulation solely in terms of the tensorial-type coordinates and their world-sheet superpartners. Properties of massless modes casting an open and a closed five-dimensional superstrings spectra are considered in brief.